Analisis Survival Faktor Risiko Gagal BayarPeserta BPJS Kesehatan Dengan Model Cox Proporsional Hazard - Resti S, Siska; Rosita, Silvia (Program Studi Aktuaria, Fakultas Sains Teknologi dan Pendidikan, Universitas Tamansiswa Padang, 2023)
The purpose of this study was to determine the risk factors that affect the failure to pay BPJS health contributions, using the Cox proportional hazard model. The study population was all BPJS participants who were registered at the Padang City Health BPJS from January 2020 to December 2020. The research sample based on a purposive sampling technique were independent BPJS health participants who were still participants in Padang City Health BPJS until this research was conducted, namely in December 2022. The results of the study show that the factors that affect the default of BPJS members in Padang City are working status, gender and BPJS class Keywords: Health BPJS, Risk Factors, Cox Proportional Hazard Model